PENGEMBANGAN DESAIN MEDIA PEMBELAJARAN SEJARAH MOVIE MAKER BERBASIS VISUALISASI SITUS MEGALITIK PUGUNG RAHARJO LAMPUNG TIMUR - Anindya Shella Rafika; Kian Amboro (Swarnadwipa, 2018)
The purpose of this research is to get Movie Maker learning media which can give detailed information about local history material of Megalithic Sites of Pugung Raharjo and also aim to strengthen awareness of local history of class X SMA N 1 Seputih Banyak. This type of research is the development of Level 1 which where in the preparation of this medium with the development method Sugiyono level 1 which only test the feasibility of the product with internal validating stage by the team of experts not to the stage of testing the students, with the preparation must also be adjusted with the analysis KI, KD and the subject matter, after the drafting process is completed then the next stage can be validated internally by a team of material and media experts.Based on the results of research, has obtained media-based visualization of Megalithic sites Pugung Raharjo which has been through the validation phase, validation is a media feasibility test developed, validation is through two stages of stage 1 and 2, which of course there are suggestions and comments for to revise the product again until it reaches the criteria worth at least score 81 and from the data obtained on the validation of material and media experts there score in stages 1 and 2, in stage 1 the material gets a percentage of 81.07% and in stage 2 with the value percentage of 92.84%.While the validation of media experts on stage 1 mstapat value of 84.69% percentage and in stage 2 got a percentage of 90.85%. From the data it can be concluded that the Movie Maker Media of Megalithic Sites Pugung Raharjo has been declared feasible and can be used to reinforce awareness of local history in students and become one of the effective and efficient media.